2019
DOI: 10.1186/s12864-019-5750-x
|View full text |Cite
|
Sign up to set email alerts
|

Waking the sleeping dragon: gene expression profiling reveals adaptive strategies of the hibernating reptile Pogona vitticeps

Abstract: Background Hibernation is a physiological state exploited by many animals exposed to prolonged adverse environmental conditions associated with winter. Large changes in metabolism and cellular function occur, with many stress response pathways modulated to tolerate physiological challenges that might otherwise be lethal. Many studies have sought to elucidate the molecular mechanisms of mammalian hibernation, but detailed analyses are lacking in reptiles. Here we examine gene expression in the Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 103 publications
2
42
0
Order By: Relevance
“…Brumation is an extreme hypometabolic state used by some reptiles to cope with low or unpredictable food availability and unfavorable seasonal conditions for the duration of winter. A number of specific protective measures have been identified during this hibernation in bearded dragons, including increased neuroprotection in the brain, maintenance of heart function through hypertrophy, and upgrading antioxidant capacity and mitochondrial maintenance by skeletal muscle atrophy [ 16 ]. Emergence from brumation may also represent a period of increased disease susceptibility in reptiles, as shown by downregulated transcription of several genes responsible for microbial pathogen defense, cellular and oxidative stress, and cell differentiation and growth [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brumation is an extreme hypometabolic state used by some reptiles to cope with low or unpredictable food availability and unfavorable seasonal conditions for the duration of winter. A number of specific protective measures have been identified during this hibernation in bearded dragons, including increased neuroprotection in the brain, maintenance of heart function through hypertrophy, and upgrading antioxidant capacity and mitochondrial maintenance by skeletal muscle atrophy [ 16 ]. Emergence from brumation may also represent a period of increased disease susceptibility in reptiles, as shown by downregulated transcription of several genes responsible for microbial pathogen defense, cellular and oxidative stress, and cell differentiation and growth [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The targets of these genes include PPARGC1A, CRTC1, CRTC2, and PRKAG1. These genes were upregulated during hibernation in all tissues with the exception of PPARGC1A, which was downregulated in brain 7 . miRNAs that target two genes important in miRNA-mediated translational repression (AGO3 and CNOT1) were downregulated during hibernation.…”
Section: Functional Analysis Of Differentially Expressed Targetsmentioning
confidence: 97%
“…Studies aiming to understand the molecular architecture of hibernation phenotype have demonstrated control at multiple levels of gene regulation: including epigenetic changes (DNA methylation and histone modification), gene silencing by microRNAs (miRNAs), and protein modifications 6,7 . Amongst these, the role of miRNAs in response to stress, such as during hibernation, is becoming increasingly evident [8][9][10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%
See 2 more Smart Citations